Temporal current-source of spikes suggests initial treatment failure in childhood absence epilepsy. (September 2015) - Yeom, Jung Sook; Kim, Young-Soo; Lee, Jun Hwa; Jung, Seokwon; Kwon, Oh-Young
Highlights: We observed current-source of spikes in childhood absence epilepsy (CAE). Frontal lobe was involved in all of the enrolled cases. Temporal lobe involvement was associated with the initial-drug failure. The information may help to estimate the efficacy of initial treatment in advance. Abstract: Purpose: In addition to the frontal lobe, the temporal lobe may also be involved in typical absence seizures. However, few studies have addressed the relationship between this involvement and drug responsiveness in childhood absence epilepsy (CAE). In this study, we observed the current-source distribution (CSD) of generalized spike-and-wave discharges (GSWDs) and investigated the relationship between temporal lobe involvement in the CSD and responsiveness to initial antiepileptic drug (AED) in CAE. Method: Seventeen consecutive patients with CAE were retrospectively enrolled in the study. Patients were divided into an initial-response group and an initial-failure group, according to their responsiveness to the initial AED treatment. For each patient, the spike peak CSD of an averaged GSWD was obtained from the initial electroencephalogram. We compared the incidence of temporal involvement in the CSD between the two groups. We also compared clinical variables, including age of onset, gender, type and dose of first AED, time to cessation of clinical seizures, and seizure-free status. Results: The initial-response and initial-failure groups contained 12 and five patients, respectively. Temporal lobe involvement was more frequent (80% vs. 17%, p = 0.03), and time to cessation of clinical seizures was more prolonged (median 2.5 months vs. 8 months, p < 0.01) in the initial-failure than in the initial-response group. None of the other variables studied differed between groups. Conclusion: Initial AED failure was associated with temporal involvement in the CSD of CAE patients. This electrophysiological information may be helpful in clinical practice by estimating the efficacy of initial AED treatment in AED-naïve CAE patients in advance.